2015
DOI: 10.1038/srep09704
|View full text |Cite
|
Sign up to set email alerts
|

Levosimendan displays anti-inflammatory effects and decreases MPO bioavailability in patients with severe heart failure

Abstract: Treatment of decompensated heart failure often includes administration of levosimendan. Myeloperoxidase (MPO) is released during polymorphonuclear neutrophil (PMN) degranulation, and mediates dysregulation of vascular tone in heart failure. We evaluated the effects of levosimendan-treatment on MPO in patients with acute decompensation of chronic heart failure over a one week course. Plasma MPO levels were significantly decreased after levosimendan treatment (from 252.1 ± 31.1 pmol/l at baseline to 215.02 ± 27.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 38 publications
0
12
1
Order By: Relevance
“…MPO activity analysis. MPO is predominantly secreted by neutrophils and can be used to determine neutrophil infiltration as an index of inflammation (20). Left lungs were obtained from rats, and the MPO activity was determined.…”
Section: Methodsmentioning
confidence: 99%
“…MPO activity analysis. MPO is predominantly secreted by neutrophils and can be used to determine neutrophil infiltration as an index of inflammation (20). Left lungs were obtained from rats, and the MPO activity was determined.…”
Section: Methodsmentioning
confidence: 99%
“…Compared with the control group, the level of NT-proBNP in the acute ischemic stroke group was higher (WMD = 1600.92, 95% CI = 607.00-2594. 84, p = 0.002, I 2 = 99%, p-value of heterogeneity <0.00001). Additionally, a significant difference in NT-proBNP was found between patients in the A maximum of two stars can be allotted in this category, one for study controls for the experimental 99 and control groups, the other for a blood collection time of <24 h. A maximum of two stars can be allotted in this category, one for study controls for the experimental 99 and control groups, the other for a blood collection time of <24 h. A maximum of two stars can be allotted in this category, one for study controls for the experimental 99 and control groups, the other for a blood collection time of <24 h. A maximum of two stars can be allotted in this category, one for study controls for the experimental 99 and control groups, the other for a blood collection time of <24 h. A maximum of two stars can be allotted in this category, one for study controls for the experimental and control groups, the other for a blood collection time of <24 h.…”
Section: Pooled Results From Literature-based Meta-analysismentioning
confidence: 92%
“…Compared with the control group, the level of NT-proBNP in the acute ischemic stroke group was 114 higher (WMD = 1600.92, 95% CI = 607.00-2594. 84, p = 0.002, I 2 = 99%, p-value of heterogeneity 115 <0.00001). Additionally, a significant difference in NT-proBNP was found between patients in the 116 hemorrhage.…”
mentioning
confidence: 93%
“…The results showed that levosimendan inhibits cardiomyocyte cytokine production and downregulates the TNF-α receptor superfamily and Fas/Fas ligand apoptotic signalling pathway. 23,24…”
Section: Myocardial Depression Factormentioning
confidence: 99%